Pengaruh Tingkat Pendidikan, Literasi Keuangan, Dan Perencanaan Keuangan Terhadap Perilaku Keuangan Umkm Di Pelataran Stadion Betoambari Kota Baubau Sulawesi Tenggara - Mardana, Faris; Fadhillah, Is (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Efforts to increase MSME knowledge include issues related to considerations in terms of financial decision making. In order to increase financial understanding, MSME actors are required to control themselves against expenses that have no long-term value. The level of education, financial literacy, and financial planning is one of the determining factors for MSME actors to be able to improve their current financial understanding. This research was conducted by distributing digital questionnaires using google forms distributed via Whatsapp social media which were filled in by 70 respondents in the Betoambari stadium yard area, Baubau City, Southeast Sulawesi in April - May 2024. The research method used in this research is quantitative method using analytical methods, namely Validation and Reliability Test, Multiple Linear Regression Analysis Test, and T Test and F Test. After testing the variables of Education Level (X1), Financial Literacy (X2), Financial Planning (X3) and Financial Behavior (Y), it resulted in variables X1 X3 partially influenced and had a positive and significant effect on variable Y but not with the results shown by variable X2 which had no partial effect on variable Y. While the results shown in the F Test the three variables simultaneously had a positive influence on the Financial Behavior variable (Y).